Analysis of Protection of Women's Rights in Marriage According to Islamic Law and Law ‑in Indonesia - Sariati (Justice Law Review, 2025)
The protection of women's rights in marriage is a crucial element in achieving justice and gender equality within the legal system. This study aims to comparatively analyze the legal protections granted to women in marriage under Islamic law and Indonesian national legislation. Employing a normative legal research method with a juridical-comparative and conceptual approach, the study draws on primary and secondary legal materials analyzed qualitatively. The findings reveal that both Islamic law and national law recognize and regulate women's rights in marriage, including the right to dowry (mahr), financial support (nafkah), protection from domestic violence, and the right to initiate divorce. However, practical implementation still faces significant challenges due to patriarchal interpretations, limited legal literacy among women, and weak access to justice. This research highlights the urgency of reinterpreting Islamic legal texts through a gender justice perspective and reforming national legal frameworks to create a more inclusive and responsive family law system. These findings are expected to serve as a foundation for policy development and further interdisciplinary research that integrates legal, social, and religious dimensions in a comprehensive manner.